The influence of media exposure on voters’ behavior during the Sumbawa 2020 local election (PILKADA) - Yadi Satriadi,; Sarina Yusuf,; Ahmad Sauffiyan Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
During Indonesia's general elections, mass media was the most popular medium for transmitting political influence. However, the extent of media influence on voting behaviour is unknown, creating a problem that necessitates careful research. As a result, the purpose of this study was to determine the impact of media exposure on voting behaviour among Sumbawa voters in Indonesia during the Pemilihan Kepala Daerah, or PILKADA 2020. A sample of 400 voters was chosen using a Multi-Level Random Sampling method. To better understand this phenomenon, a set of questionnaires was used as a data collection tool in the field. The collected data was then analysed using SPSS software version 26. Descriptive analysis revealed that the level of media exposure was divided into three categories: low, medium, and high. However, such exposure has only a minor impact on voter behaviour. While inferential analysis shows that non-mass media exposure has a significant influence on the voting behaviour of the Sumbawa community in PILKADA 2020. This strengthens the case that the media has a direct influence on voting behaviour, as opposed to previous theories that based their argument on social and cultural variables. In conclusion, this study concludes that, when compared to mass media, respondents in this area prefer online media and media such as billboards or banners, posters, calendars, or stickers as a source of political information.